Investigation on the mitigation of earthquake hazards with inclusion of tire wastes into the sand - Yıldız, Özgür, 1976- (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
With the development of technology, tire wastes disposed in the environment, cause serious problems. In the 21st century, cost, environment and seismic performance are going to be most important factors in the design, construction and retrofitting of structures against to earthquake loadings. Tire wastes have many properties which result in their being of value from a civil and geotechnical engineering perspective: low density, high strength, thermal insulation, energy absorption capacity, permeability, durability, compressibility, resilience and high frictional strength. It is due to these properties, the use of tire wastes are yet to be exploited in common civil engineering applications such as lightweight material for backfill of retaining structures, drainage layer, thermal insulation layer or seismic isolation layer. Also, it is well known to utilize tire waste derived recycled scrap tires to minimize the earthquake related hazards of structures. The main objective of this study is to develop a new technique to mitigate earthquake induced liquefaction hazards by utilizing different tire waste with different ratios, shapes and aspect ratios. In this study, a series of laboratory tests are performed to evaluate the liquefaction susceptibility of soil and to determine engineering properties of specimens. A flexible shear stack is designed and constructed to be used in shaking table tests. A set of shaking table tests is performed at different temperatures to investigate the liquefaction mitigation effect of tire waste inclusion under different thermal conditions. These shaking table tests are conducted at Shaking Table Laboratory of Kandilli Observatory and Earthquake Research Institute. As a result of these laboratory studies, the liquefaction mitigation effect of different type of tire wastes are investigated. The test results also demonstrated that the proposed mitigation method not only minimizes liquefaction effect but also reduces the earthquake induced permanent displacement of structures.
Keywords: Waste products as road materials.; Tires -- Recycling.